Radical Propaganda and Counter-Narrative in Shamsie’s Novel Home Fire: The Case of Parvaiz Pasha - Nada Syifa Fitriani; Hasnul Insani Djohar (Leksema: Jurnal Bahasa dan Sastra, 2026)
This research analyzes how narrative propaganda is used by Farooq's character to recruit Parvaiz Pasha in Kamila Shamsie's Home Fire, and how these narratives can be countered through ideological and affective approaches. The background of this research is based on the increasing phenomenon of radicalization that is not only caused by political or economic factors, but also by the power of narratives that shape a person's identity and meaning of life. The purpose of this research is to uncover three forms of Farooq's propaganda narratives containing familial legacy, masculine struggle, and utopian promise, and construct a counter-narrative that can challenge and undermine these ideological influences. This research uses Luc Herman and Bart Vervaeck's theory of narrative as ideology, which explains that narratives are never neutral, but always carry certain values and ideologies. The theory is supported by Jowett and O'Donnell's concept of propaganda, which emphasizes the importance of symbolic strategies in influencing perceptions, and Henry Giroux's concept of counter-narrative, which sees counter-narrative as a form of cultural resistance and critical education. The method used is narrative analysis with a qualitative textual analysis approach, focusing on character dialog and narrative description in the text in Parvaiz Pasha's chapter. The results show that Farooq's propaganda is effective as it exploits Parvaiz's emotional emptiness and search for meaning. However, the narrative can be countered through the affirmation of individual agency, the redefinition of family love as a progressive force, and the recognition of the complexity of life that cannot be simplified by ideological promises. In conclusion, counter-narratives that are reflective, supportive, and contextual can be an important strategy in preventing the influence of extremist propaganda in the realm of fiction and social reality.